Super-hydrophobic metal organic framework composite material as well as preparation method and application thereof
Through the amidation reaction of the amino-modified ZIF material and polylactic acid, a superhydrophobic metal organic framework composite with hydrophobicity and stability is formed, which solves the problems of poor material stability and complex preparation in the prior art, and achieves low-cost and environmentally friendly Material preparation and application.
Patent Information
- Application Number
- CN202411745968.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing metal organic framework materials have poor stability in moisture environments, and the existing modification strategies have problems such as high cost, unfriendly environment, and complex preparation, making them difficult to achieve widespread application.
The amino-modified ZIF material and polylactic acid are used to react with amidation to form a superhydrophobic metal organic framework composite material. By optimizing the number average molecular weight and amidation reaction conditions of polylactic acid, it ensures that the polylactic acid is firmly coated on the surface of the ZIF material and enhances the material's Hydrophobicity and stability.
It has achieved a superhydrophobic metal organic framework composite material with low cost, good hydrophobicity and good stability. It has excellent hydrothermal stability and no secondary pollution, and is suitable for large-scale preparation and industrial applications.
Smart Images

Figure CN119219927A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal organic framework composite material preparation, and relates to a super hydrophobic metal organic framework composite material and a preparation method and application thereof. Background Art
[0002] Metal-organic framework materials (MOFs) are porous crystalline materials with wireless network structures formed by self-assembly of metal ions or metal clusters and organic ligands through coordination bonds, also known as porous coordination polymers. MOFs belong to the family of porous materials with inorganic-organic hybrid components, combining the rigidity of inorganic materials and the flexibility of organic materials. They have advantages such as nanoscale pores, strong acid-base catalytic activity, large specific surface area, multiple metal sites, and adjustable pore structure. They are widely used in gas adsorption and separation, gas storage, catalysis, sensing, and medicine.
[0003] The metal nodes and ligands in MOFs are connected by weak coordination bonds, which makes MOFs vulnerable to chemical environmental changes, especially in strong acid and alkaline environments, leading to the collapse of the MOF structure and loss of performance, significantly limiting its effectiveness in applications under water conditions, such as gas / liquid storage and separation, catalysis, biomedicine, etc. Therefore, improving the stability of MOFs materials has become a key challenge in promoting their transition from laboratory research to industrial applications.
[0004] At present, there are two main strategies to improve the stability of MOFs materials: one is to rationally design ligands and metal ions, that is, through the careful selection and design of organic ligands and metal ions, including the selection of metal ions with strong coordination ability, such as high-valent metal ions, which can form more stable coordination bonds with organic ligands. Or optimize the structure of organic ligands, introduce rigid groups or increase the interaction between ligands to enhance the overall stability of MOFs. However, the selection range of ligands and metal ions is limited, and they have high cost, low availability, and complex design process. The second is to modify the surface of MOFs. By introducing one or more layers of protective layers such as polymers, inorganic oxides or carbon materials on the surface of MOFs particles, the MOFs particles are completely wrapped in a stable hydrophobic shell, which can effectively block the penetration of liquid water and significantly reduce the direct contact between MOFs pores and water molecules to isolate them from the external environment. Corrosion, without changing the internal structure and performance of MOFs, significantly improve its stability. However, in the above strategies, the protective layer is mainly modified on the surface of MOFs particles through van der Waals forces and other forms, which has defects such as poor structural stability. If used for a long time, especially in an aqueous environment for a long time, the protective layer will fall off from the surface of MOFs particles, resulting in a decrease in hydrophobicity, which in turn makes the stability of MOFs materials worse. In addition, the polymers used are usually environmentally unfriendly, toxic, and prone to secondary pollution. At the same time, the preparation conditions are harsh, the preparation process is complex, and the preparation cost is high, resulting in expensive products, which is not conducive to the widespread use of MOFs materials. Therefore, the development of a low-cost, good hydrophobic, stable, green and environmentally friendly super-hydrophobic metal-organic framework composite material and a matching preparation process with simple process, convenient operation, and no secondary pollution is of practical significance for improving the stability of MOFs materials and promoting their widespread application. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a low-cost, good hydrophobicity, good stability, green and environmentally friendly super-hydrophobic metal-organic framework composite material and a preparation method and application thereof.
[0006] In order to solve the above technical problems, the present invention adopts the following technical solutions: A method for preparing a super-hydrophobic metal-organic framework composite material comprises the following steps: S1, providing an amino-modified ZIF material; S2, mixing the amino-modified ZIF material with polylactic acid for amidation reaction to obtain a super-hydrophobic metal organic framework composite material; the number average molecular weight of the polylactic acid is 1.0×10 5 g / mol~2.5×10 5 g / mol.
[0007] The above preparation method is further improved, in step S2, the number average molecular weight of the polylactic acid is 1.5×10 5 g / mol~2.0×10 5 g / mol.
[0008] The above preparation method is further improved, in step S2, the polylactic acid is mixed with the amino-modified ZIF material in the form of a polylactic acid solution.
[0009] The above preparation method is further improved in that the ratio of the mass of the amino-modified ZIF material to the volume of the polylactic acid solution is 0.2 mg to 0.7 mg: 1 mL; The above preparation method is further improved in that the polylactic acid solution is prepared by dissolving polylactic acid in dichloromethane.
[0010] The above preparation method is further improved in that the mass fraction of the polylactic acid in the polylactic acid solution is 0.07wt% to 0.2wt%.
[0011] The above preparation method is further improved in that the ratio of the mass of the amino-modified ZIF material to the volume of the polylactic acid solution is 0.3 mg to 0.6 mg: 1 mL.
[0012] The above preparation method is further improved in that the mass fraction of the polylactic acid in the polylactic acid solution is 0.1wt% to 0.15wt%.
[0013] The above preparation method is further improved, in step S1, the amino-modified ZIF material includes at least one of NH2-ZIF-67 and NH2-ZIF-8.
[0014] The above preparation method is further improved, and the preparation method of NH2-ZIF-67 comprises the following steps: (1.1) Dissolve a cobalt salt in methanol to prepare a cobalt salt solution; dissolve 2-aminobenzimidazole and 2-methylimidazole in methanol to obtain a ligand solution A; the ratio of the cobalt salt to the methanol is 0.5 g to 0.8 g: 50 mL; the cobalt salt is cobalt nitrate hexahydrate; the ratio of the 2-aminobenzimidazole to the 2-methylimidazole to the methanol is 0.4 g to 0.6 g: 1 g to 1.4 g: 50 mL; (1.2) Mix the cobalt salt solution and ligand solution A, stir for 1 h to 2 h, centrifuge at 4500 r / min to 6000 r / min for 3 min to 5 min, wash with methanol, repeat the centrifugation and washing three times each, and dry at 40°C to 80°C for 10 h to 15 h to obtain NH2-ZIF-67 solid powder.
[0015] The above preparation method is further improved, and the preparation method of NH2-ZIF-8 comprises the following steps: (2.1) Dissolve a zinc salt in methanol to prepare a zinc salt solution; dissolve 2-aminobenzimidazole and 2-methylimidazole in methanol to obtain a ligand solution B; the ratio of the zinc salt to methanol is 0.6 g to 0.8 g: 50 mL; the zinc salt is zinc nitrate hexahydrate; the ratio of the 2-aminobenzimidazole to the 2-methylimidazole to the methanol is 0.4 g to 0.6 g: 1 g to 1.4 g: 50 mL; (2.2) Mix the zinc salt solution and ligand solution B, stir for 1 h to 2 h, centrifuge at 4500 r / min to 6000 r / min for 3 min to 5 min, wash with methanol, repeat the centrifugation and washing three times each, and dry at 40°C to 80°C for 10 h to 15 h to obtain NH2-ZIF-8 solid powder.
[0016] The above preparation method is further improved. In step S2, the amidation reaction is carried out at a temperature of 30°C to 60°C; the amidation reaction time is 6h to 15h; after the amidation reaction is completed, the product is subjected to the following treatment: centrifugation at a speed of 4500 r / min to 6000 r / min for 3 min to 5 min, washing with ethanol, and drying at 40°C to 80°C for 10 h to 15 h to obtain a superhydrophobic metal-organic framework composite material.
[0017] The above preparation method is further improved, in step S2, the amidation reaction is carried out at a temperature of 40°C to 50°C; the amidation reaction time is 8h to 12h.
[0018] As a general technical concept, the present invention also provides a super-hydrophobic metal-organic framework composite material, which is prepared by the above-mentioned preparation method.
[0019] As a general technical concept, the present invention also provides an application of the above-mentioned super-hydrophobic metal-organic framework composite material in treating wastewater, purifying air or preparing sensors.
[0020] Compared with the prior art, the advantages of the present invention are: (1) In view of the defects of existing metal organic framework materials such as poor hydrophobicity, harsh preparation conditions and complex preparation process, the present invention provides a method for preparing a super hydrophobic metal organic framework composite material with a number average molecular weight of 1.0×10 5 g / mol~2.5×10 5g / mol of polylactic acid is used as a modifier to modify the amino-modified ZIF material. Specifically, during the amidation reaction, the amino group in the amino-modified ZIF material is chemically reacted with the -OH group at the end of the polylactic acid to remove a molecule of water, thereby forming an amide bond, so that the polylactic acid is tightly bonded to the surface of the amino-modified ZIF material. Not only can the polylactic acid be used to improve the hydrophobicity of the surface of the ZIF material, but the polylactic acid can also be effectively prevented from falling off, thereby preparing a super-hydrophobic metal-organic framework composite material with good hydrophobicity and stability. The contact angle of the super-hydrophobic metal-organic framework composite material can be increased to 160°, and the rolling angle can be reduced to 4°, showing very excellent super-hydrophobic performance. Moreover, the composite material has good hydrothermal stability, can exclude liquid water, and can reduce the adhesion of water on the surface of the amino-modified ZIF material, which is beneficial for the amino-modified ZIF material to exert its performance advantages. On this basis, in the present invention, by optimizing the molecular weight of polylactic acid, it is possible to effectively avoid the clogging of the pores of the material by the hydrophobic groups, maintain the unique pore chemical properties and structure of the material, and promote the high performance advantages, thereby preparing a super-hydrophobic metal-organic framework composite material with good hydrophobicity and stability. In particular, when the number average molecular weight of polylactic acid is less than 1.0×10 5 g / mol, the amount of polylactic acid bonded to the surface of the ZIF material is less, and the hydrophobicity of the modified ZIF material is poor. When the number average molecular weight of polylactic acid is greater than 2.5×10 5 When g / mol, the polylactic acid of ZIF material surface bonding is too much, causing part of polylactic acid to fall off, and hydrophobicity is reduced. In addition, compared with other polymers, the polylactic acid adopted in the present invention is a kind of biodegradable polymer, with good biocompatibility and degradability, non-toxic to human body, easy to biodegradation, which makes the super-hydrophobic metal organic framework composite material of the present invention have the characteristics such as low cost, environmental friendliness, no secondary pollution. Meanwhile, preparation method of the present invention also has the advantages such as simple process, easy operation and gentle preparation conditions, is suitable for large-scale preparation, and is convenient to industrial application.
[0021] (2) In the preparation method of the present invention, the number average molecular weight of polylactic acid is further optimized to be 1.5×10 5 g / mol~2.0×10 5 g / mol, the composite material thus prepared has better hydrophobicity and thus has better stability.
[0022] (3) In the preparation method of the present invention, the use of polylactic acid is also optimized. Specifically, the polylactic acid solution is mixed with the amino-modified ZIF material, which is more conducive to the uniform distribution of polylactic acid on the surface of the amino-modified ZIF material. At the same time, the amount of polylactic acid is also optimized, which is conducive to regulating the amount of polylactic acid coated on the surface of the amino-modified ZIF material. While ensuring that the polylactic acid is firmly coated on the surface of the amino-modified ZIF material, the hydrophobicity of the composite material can be significantly improved, so that the prepared composite material has more excellent superhydrophobic performance and stability. In particular, by optimizing the amount of polylactic acid, it is possible to effectively avoid polylactic acid blocking the pores of the amino-modified ZIF material, thereby being more conducive to exerting the performance advantages of the metal organic framework material.
[0023] (4) In the preparation method of the present invention, by optimizing the conditions of the amidation reaction, an appropriate amount of polylactic acid can be firmly coated on the surface of the ZIF material, thereby further improving the hydrophobicity and stability of the polylactic acid to the amino-modified ZIF material, thereby facilitating the preparation of a superhydrophobic metal-organic framework composite material with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0025] Figure 1 1 is the XRD diagram of NH2-ZIF-67 and modified NH2-ZIF-67 prepared in Example 1 of the present invention.
[0026] Figure 2 IR spectra of NH2-ZIF-67 and modified NH2-ZIF-67 prepared in Example 1 of the present invention.
[0027] Figure 3a-3b SEM images of NH2-ZIF-67 (a) and modified NH2-ZIF-67 (b) prepared in Example 1 of the present invention.
[0028] Figure 4a-4b Graphs showing the water contact angle test results of NH2-ZIF-67 (a) and modified NH2-ZIF-67 (b) prepared in Example 1 of the present invention.
[0029] Figure 5 1 is the XRD diagram of NH2-ZIF-67 and modified NH2-ZIF-67 prepared in Example 1 of the present invention after chemical stability test.
[0030] Figure 6 The XRD diagrams of ZIF-8 and modified ZIF-8 prepared in Comparative Example 5 after chemical stability testing.
[0031] Figure 7 XRD diagrams of NH2-UiO-66 and modified NH2-UiO-66 prepared in Comparative Example 6 after chemical stability test. DETAILED DESCRIPTION
[0032] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments of the specification, but the protection scope of the present invention is not limited thereby. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The "range" disclosed in the present invention can be defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can be inclusive or exclusive of the end values, and any end value can be included or excluded independently, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a specific parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are also listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present invention, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, wherein a and b are both real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" have been listed in this article, and "0-5" is just an abbreviation of these numerical combinations.
[0034] In the present invention, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0035] If not otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form a new technical solution.
[0036] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present invention. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. Reference to "implementations" herein has a similar understanding.
[0037] Those skilled in the art will appreciate that, in the methods of various embodiments or examples, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present invention can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0038] In the present invention, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0039] In the present invention, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel solutions of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0040] In view of the defects of existing metal organic framework materials such as poor hydrophobicity, harsh preparation conditions and complex preparation process, the present invention provides a super hydrophobic metal organic framework composite material and its preparation method and application, aiming to obtain a super hydrophobic metal organic framework composite material with low cost, good hydrophobicity, good stability and green environmental protection.
[0041] In a first aspect, the present invention provides a method for preparing a super-hydrophobic metal-organic framework composite material, comprising the following steps: S1, providing an amino-modified ZIF material; S2, mixing the amino-modified ZIF material with polylactic acid for amidation reaction to obtain a super-hydrophobic metal organic framework composite material, wherein the number average molecular weight of the polylactic acid is 1.0×105 g / mol~2.5×10 5 g / mol.
[0042] It can be understood that as a superhydrophobic material, the superhydrophobic metal-organic framework composite material has a surface stable contact angle greater than 150° and a rolling contact angle less than 10°.
[0043] Understandably, the amino-modified ZIF material used can be homemade or commercially available, and is a ZIF material with an amino (NH2) group modified on the surface, wherein the ZIF material (Zeolitic Imidazolate Frameworks) is a MOFs having a zeolite-like structure formed by the reaction of metal ions (such as zinc ions or cobalt ions) with imidazole ligands. Furthermore, the amino-modified ZIF material in the present invention is obtained by self-assembly of an imidazole organic ligand containing an amino group and a metal ion (such as a zinc ion or a cobalt ion).
[0044] Understandably, polylactic acid is a high molecular polymer, but it is different from conventional polymers and has the following advantages: (a) Good biodegradability. Compared with conventional polymers, polylactic acid has significantly better degradation performance, which helps reduce plastic pollution and solid waste treatment pressure. (b) Good environmental protection. Polylactic acid does not contain plasticizers, heavy metals and toxic chemicals, nor does it contain bisphenol A. It is an environmentally friendly material. Its production raw materials are mainly derived from renewable plant resources (such as corn, cassava, etc.), and do not rely on petroleum resources, which helps reduce carbon emissions and energy consumption. (c) It has good biocompatibility and degradability.
[0045] As an example, in the preparation method of the super-hydrophobic metal organic framework composite material of the present invention, the number average molecular weight is 1.0×10 5 g / mol~2.5×10 5g / mol of polylactic acid is used as a modifier to modify the amino-modified ZIF material. Specifically, during the amidation reaction, the amino group in the amino-modified ZIF material is chemically reacted with the -OH group at the end of the polylactic acid to remove a molecule of water, thereby forming an amide bond, so that the polylactic acid is tightly bonded to the surface of the amino-modified ZIF material. Not only can the polylactic acid be used to improve the hydrophobicity of the surface of the amino-modified ZIF material, but the polylactic acid can also be effectively prevented from falling off, thereby preparing a super-hydrophobic metal-organic framework composite material with good hydrophobicity and stability. The contact angle of the super-hydrophobic metal-organic framework composite material can be increased to 160°, and the rolling angle can be reduced to 4°, showing very excellent super-hydrophobic performance. Moreover, the composite material has good hydrothermal stability, can exclude liquid water, and can reduce the adhesion of water on the surface of the amino-modified ZIF material, which is beneficial for the amino-modified ZIF material to exert its performance advantages. On this basis, in the present invention, by optimizing the molecular weight of polylactic acid, it is possible to effectively avoid that hydrophobic groups cause blockage to the pores of materials, keep the pore chemical properties and structure of the material, promote the performance advantage of high efficiency, thus prepare the super-hydrophobic metal organic framework composite material with good hydrophobicity and good stability. In addition, compared with other polymers, the polylactic acid used in the present invention is a kind of biodegradable polymer, with good biocompatibility and degradability, non-toxic to human body, easy to biodegradable, and this makes the super-hydrophobic metal organic framework composite material of the present invention have the characteristics of low cost, environmental friendliness, no secondary pollution. Meanwhile, preparation method of the present invention also has the advantages of simple process, easy operation and gentle preparation conditions, is suitable for large-scale preparation, and is convenient to industrial application.
[0046] In some embodiments, the number average molecular weight of polylactic acid is 1.0×10 5 g / mol~2.5×10 5 As an example, the number average molecular weight of polylactic acid can be 1.0×10 5 g / mol, 1.2×10 5 g / mol, 1.4×10 5 g / mol, 1.5×10 5 g / mol, 1.7×10 5 g / mol, 1.8×10 5 g / mol, 1.9×10 5 g / mol, 2.0×10 5 g / mol, 2.1×10 5 g / mol, 2.3×10 5 g / mol, 2.4×10 5 g / mol, 2.5×10 5g / mol, or it can be within the range formed by any two of the above point values as end values. Optionally, the number average molecular weight of polylactic acid is 1.5×10 5 g / mol~2.0×10 5 g / mol.
[0047] In the preparation method of the present invention, the number average molecular weight of polylactic acid is further optimized to be 1.5×10 5 g / mol~2.0×10 5 g / mol, the composite material thus prepared has better hydrophobicity and thus has better stability. In particular, when the number average molecular weight of polylactic acid is less than 1.0×10 5 g / mol, the amount of polylactic acid bonded to the surface of the amino-modified ZIF material is less, and the hydrophobicity of the obtained modified ZIF material is poor; when the number average molecular weight of polylactic acid is greater than 2.5×10 5 When the hydrophobicity is 0.0447 W / mol, there is too much polylactic acid bonded to the surface of the amino-modified ZIF material, which causes part of the polylactic acid to fall off and reduces the hydrophobicity.
[0048] Optionally, the polylactic acid is mixed with the amino-modified ZIF material in the form of a polylactic acid solution. As an example, mixing the polylactic acid solution with the amino-modified ZIF material is more conducive to uniform distribution of the polylactic acid on the surface of the amino-modified ZIF material.
[0049] In some embodiments, the ratio of the mass of the amino-modified ZIF material to the volume of the polylactic acid solution is 0.2 mg to 0.7 mg: 1 mL. As an example, the ratio of the mass of the amino-modified ZIF material to the volume of the polylactic acid solution may be 0.2 mg: 1 mL, 0.3 mg: 1 mL, 0.4 mg: 1 mL, 0.5 mg: 1 mL, 0.6 mg: 1 mL, 0.7 mg: 1 mL, or may be within the range of any two of the above point values as end values. Optionally, the ratio of the mass of the amino-modified ZIF material to the volume of the polylactic acid solution is 0.3 mg to 0.6 mg: 1 mL.
[0050] Optionally, the polylactic acid solution is prepared by dissolving polylactic acid in dichloromethane.
[0051] In some embodiments, the mass fraction of polylactic acid in the polylactic acid solution is 0.07wt% to 0.2wt%. As an example, the mass fraction of polylactic acid in the polylactic acid solution may be 0.07wt%, 0.08wt%, 0.09wt%, 0.10wt%, 0.12wt%, 0.14wt%, 0.15wt%, 0.17wt%, 0.18wt%, 0.19wt%, 0.20wt%, or any two of the above points may be used as end values. Optionally, the mass fraction of polylactic acid in the polylactic acid solution is 0.1wt% to 0.15wt%.
[0052] In the preparation method of the present invention, by optimizing the amount of polylactic acid used, it is beneficial to regulate the coating amount of polylactic acid on the surface of the amino-modified ZIF material, and while ensuring that the polylactic acid is firmly coated on the surface of the amino-modified ZIF material, the hydrophobicity of the composite material can also be significantly improved, so that the prepared composite material has more excellent superhydrophobic performance and stability. In particular, by optimizing the amount of polylactic acid used, it is possible to effectively avoid polylactic acid blocking the pores of the amino-modified ZIF material, thereby being more conducive to exerting the performance advantages of the metal organic framework material.
[0053] In some embodiments, the amino-modified ZIF material includes at least one of NH2-ZIF-67 and NH2-ZIF-8. As an example, the amino-modified ZIF material may be NH2-ZIF-67, NH2-ZIF-8.
[0054] Optionally, the preparation method of NH2-ZIF-67 comprises the following steps: (1.1) Dissolve cobalt salt in methanol to prepare a cobalt salt solution; dissolve 2-aminobenzimidazole and 2-methylimidazole in methanol to obtain a ligand solution A.
[0055] (1.2) Mix the cobalt salt solution and ligand solution A, stir for 1 h to 2 h, centrifuge at 4500 r / min to 6000 r / min for 3 min to 5 min, wash with methanol, repeat the centrifugation and washing three times each, and dry at 40°C to 80°C for 10 h to 15 h to obtain NH2-ZIF-67 solid powder.
[0056] Optionally, in step (1.1), the ratio of cobalt salt to methanol is 0.5 g to 0.8 g: 50 mL.
[0057] Optionally, in step (1.1), the cobalt salt is cobalt nitrate hexahydrate.
[0058] Optionally, in step (1.1), the ratio of 2-aminobenzimidazole, 2-methylimidazole and methanol is 0.4 g to 0.6 g: 1 g to 1.4 g: 50 mL.
[0059] Optionally, the preparation method of NH2-ZIF-8 comprises the following steps: (2.1) Dissolve zinc salt in methanol to prepare a zinc salt solution; dissolve 2-aminobenzimidazole and 2-methylimidazole in methanol to obtain a ligand solution B; (2.2) Mix the zinc salt solution and ligand solution B, stir for 1 h to 2 h, centrifuge at 4500 r / min to 6000 r / min for 3 min to 5 min, wash with methanol, repeat the centrifugation and washing three times each, and dry at 40°C to 80°C for 10 h to 15 h to obtain NH2-ZIF-8 solid powder.
[0060] Optionally, in step (2.1), the ratio of zinc salt to methanol is 0.6 g to 0.8 g: 50 mL.
[0061] Optionally, in step (2.1), the zinc salt is zinc nitrate hexahydrate.
[0062] Optionally, in step (2.1), the ratio of 2-aminobenzimidazole, 2-methylimidazole and methanol is 0.4 g to 0.6 g: 1 g to 1.4 g: 50 mL.
[0063] In some embodiments, in step S2, the amidation reaction is carried out at a temperature of 30°C to 60°C. As an example, the amidation reaction can be carried out at a temperature of 30°C, 35°C, 40°C, 45°C, 50°C, 50°C, 60°C, or within a range consisting of any two of the above point values as end values. Optionally, the amidation reaction is carried out at a temperature of 40°C to 50°C.
[0064] In some embodiments, in step S2, the amidation reaction time is 6 h to 15 h. As an example, the amidation reaction time can be 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, 13 h, 14 h, 15 h, or can be within the range of any two of the above point values as end values. Optionally, the amidation reaction time is 8 h to 12 h.
[0065] In the preparation method of the present invention, by optimizing the conditions of the amidation reaction, an appropriate amount of polylactic acid can be firmly coated on the surface of the amino-modified ZIF material, thereby further improving the hydrophobicity and stability of the polylactic acid to the amino-modified ZIF material, thereby facilitating the preparation of a super-hydrophobic metal-organic framework composite material with excellent performance.
[0066] Optionally, after the amidation reaction is completed, the product is treated as follows: the product after the amidation reaction is placed in a centrifuge, centrifuged at a speed of 4500 r / min to 6000 r / min for 3 min to 5 min, washed with ethanol, and dried at 40°C to 80°C for 10 h to 15 h to obtain a superhydrophobic metal-organic framework composite material.
[0067] In addition, compared with conventional modified metal organic framework materials, in the preparation method of the present invention, the amino-modified ZIF material is modified by polylactic acid, and the obtained modified ZIF material also has the following advantages: (a) complementary properties, amino-modified ZIF materials (such as ZIF-8) have large specific surface area, good adsorption performance and molecular recognition, so polylactic acid and amino-modified ZIF materials are combined to form a composite material, and then by utilizing the adsorption performance of amino-modified ZIF materials, the polylactic acid can improve the capture ability of specific substances (such as heavy metal ions, nuclear elements, etc.). (b) strong biocompatibility, amino-modified ZIF materials and polylactic acid both have good biocompatibility, so after combining them together, the biocompatibility of the composite material can be further improved, which helps to broaden the application range of the composite material in the biomedical field, such as for manufacturing safer medical implants or drug sustained release systems. (c) Regulation of degradation performance: By adjusting the type of amino-modified ZIF material, the molecular weight and content of polylactic acid, the degradation performance of the composite material can be regulated, which helps to meet the requirements of material degradation rate in different application scenarios and improve the practicality and application range of the material.
[0068] In a second aspect, the present invention provides a super-hydrophobic metal-organic framework composite material prepared by the preparation method of the first aspect.
[0069] In a third aspect, the present invention provides an application of the superhydrophobic metal-organic framework composite material of the second aspect in treating wastewater, purifying air, and preparing sensors.
[0070] Optionally, when the above-mentioned super-hydrophobic metal organic framework composite material is used to process wastewater, including for processing oily wastewater, heavy metal wastewater. As an example, when using super-hydrophobic metal organic framework composite material to process oily wastewater, the adsorption performance and hydrophobicity of super-hydrophobic metal organic framework composite material can be used to efficiently remove grease and organic pollutants from water, and realize the effective separation of oil and water, and is suitable for the fields such as industrial wastewater treatment, cleaning after oil spill at sea. As an example, when using super-hydrophobic metal organic framework composite material to process heavy metal wastewater, the adsorption performance and hydrophobicity of super-hydrophobic metal organic framework composite material can be used to remove impurities and pollutants in water, such as heavy metal ions and other harmful substances can be removed in water body, which is conducive to improving water quality, and is of great significance for realizing the effective purification of wastewater.
[0071] Alternatively, the above-mentioned super-hydrophobic metal organic framework composite material is used to purify air. As an example, the super-hydrophobic metal organic framework composite material is used to purify indoor air, by utilizing the hydrophilicity, water adsorption capacity and stability of the super-hydrophobic metal organic framework composite material, it is possible to absorb and release moisture within a suitable humidity range, the indoor humidity can be automatically adjusted, and the comfort of the indoor environment is maintained, and at the same time, indoor pollutants, such as harmful gases such as formaldehyde and benzene, can also be captured and removed, to improve indoor air quality. As an example, some gas molecules can be selectively adsorbed using a super-hydrophobic metal organic framework composite material to achieve effective separation and purification of gas.
[0072] Optionally, the superhydrophobic metal-organic framework composite material is used to prepare a sensor.
[0073] In the following examples of the present invention, unless otherwise specified, the materials and instruments used are commercially available, the equipment used is conventional equipment, and the data obtained are the average values of more than three repeated experiments.
[0074] Example 1 A method for preparing a super-hydrophobic metal organic framework composite material, specifically using polylactic acid to modify the surface of NH2-ZIF-67 material, comprising the following steps: (1) Synthesis of NH2-ZIF-67: 0.728 g of cobalt nitrate hexahydrate was dissolved in 50 mL of methanol to obtain a cobalt nitrate solution. 0.549 g of 2-aminobenzimidazole and 1.340 g of 2-methylimidazole were dissolved in 50 mL of methanol to obtain a ligand solution A. The cobalt nitrate solution and the ligand solution A were mixed and stirred for 1.5 h to obtain a purple suspension, which was centrifuged at 5000 r / min for 4 min and washed with methanol. The centrifugation and washing were repeated three times each, and dried at 80°C for 12 h to obtain NH2-ZIF-67 solid powder, which was recorded as NH2-ZIF-67.
[0075] (2) Synthesis of superhydrophobic metal-organic framework composites: The number average molecular weight is 1.9×10 5g / mol polylactic acid (PLA) masterbatch was dissolved in 20 mL dichloromethane, and ultrasonicated for 30 min to completely dissolve it to obtain a polylactic acid solution with a mass concentration of 0.1wt%. 10 mg NH2-ZIF-67 solid powder was added to the above polylactic acid solution, heated to 45°C and stirred for 12 h, that is, amidation reaction was carried out at 45°C for 12 h, and the reaction product was placed in a centrifuge at a speed of 5000 r / min for 4 min, the supernatant was removed, washed with ethanol, and dried at 80°C for 12 h to obtain a superhydrophobic metal organic framework composite material, which was recorded as modified NH2-ZIF-67.
[0076] Example 2 A method for preparing a super-hydrophobic metal organic framework composite material is basically the same as that in Example 1, except that the number average molecular weight of polylactic acid (PLA) is 1.0×10 5 g / mol.
[0077] Example 3 A method for preparing a super-hydrophobic metal organic framework composite material is basically the same as that in Example 1, except that the number average molecular weight of polylactic acid (PLA) is 2.5×10 5 g / mol.
[0078] Example 4 A method for preparing a super-hydrophobic metal organic framework composite material is basically the same as that in Example 1, except that the number average molecular weight of polylactic acid (PLA) is 1.5×10 5 g / mol.
[0079] Example 5 A method for preparing a super-hydrophobic metal organic framework composite material is basically the same as that in Example 1, except that the number average molecular weight of polylactic acid (PLA) is 2.0 × 10 5 g / mol.
[0080] Example 6 A method for preparing a super-hydrophobic metal-organic framework composite material is substantially the same as that of Example 1, except that the mass concentration of the polylactic acid (PLA) solution is 0.07 wt %.
[0081] Example 7 A method for preparing a super-hydrophobic metal-organic framework composite material is substantially the same as that of Example 1, except that the mass concentration of the polylactic acid (PLA) solution is 0.15 wt %.
[0082] Example 8 A method for preparing a super-hydrophobic metal-organic framework composite material is substantially the same as that of Example 1, except that the mass concentration of the polylactic acid (PLA) solution is 0.2 wt %.
[0083] Example 9 A method for preparing a super-hydrophobic metal organic framework composite material, specifically using polylactic acid to modify the surface of NH2-ZIF-8 material, comprising the following steps: (1) Synthesis of NH2-ZIF-8: 0.745 g of zinc nitrate hexahydrate was dissolved in 50 mL of methanol to obtain zinc nitrate solution. 0.549 g of 2-aminobenzimidazole and 1.340 g of 2-methylimidazole were dissolved in 50 mL of methanol to obtain ligand solution B. The zinc nitrate solution and ligand solution B were mixed and stirred for 1.5 h to obtain a purple suspension, which was centrifuged at 5000 r / min for 4 min and washed with methanol. The centrifugation and washing were repeated three times each, and dried at 80°C for 12 h to obtain NH2-ZIF-8 solid powder, which was recorded as NH2-ZIF-8.
[0084] (2) Synthesis of superhydrophobic metal-organic framework composites: The number average molecular weight is 1.9×10 5 g / mol polylactic acid (PLA) masterbatch was dissolved in 20 mL dichloromethane, and ultrasonicated for 30 min to completely dissolve it, to obtain a polylactic acid solution with a mass concentration of 0.1wt%. 10 mg NH2-ZIF-8 solid powder was added to the above polylactic acid solution, heated to 45 ° C and stirred for 12 h, that is, amidation reaction was carried out at 45 ° C for 12 h, and the reaction product was placed in a centrifuge at a speed of 5000 r / min for 4 min, the supernatant was removed, washed with ethanol, and dried at 80 ° C for 12 h to obtain a superhydrophobic metal organic framework composite material, which was recorded as modified NH2-ZIF-8.
[0085] Example 10 A method for preparing a super-hydrophobic metal-organic framework composite material is basically the same as that in Example 1, except that the amidation reaction time is 6 hours.
[0086] Embodiment 11 A method for preparing a super-hydrophobic metal-organic framework composite material is basically the same as that in Example 1, except that the amidation reaction time is 9 hours.
[0087] Example 12 A method for preparing a super-hydrophobic metal-organic framework composite material is basically the same as that in Example 1, except that the amidation reaction time is 15 hours.
[0088] Comparative Example 1 A method for preparing NH2-ZIF-67 is the same as that in Example 1.
[0089] Comparative Example 2 A method for preparing ZIF-67 is the same as the method for preparing NH2-ZIF-67 in Example 1, except that 2-aminobenzimidazole is replaced by 2-methylimidazole.
[0090] Comparative Example 3 A method for preparing a hydrophobic metal organic framework composite material is basically the same as Example 1, except that: in Comparative Example 3, the number average molecular weight of polylactic acid is 0.5×10 5 g / mol.
[0091] Comparative Example 4 A method for preparing a hydrophobic metal organic framework composite material is basically the same as Example 1, except that: in Comparative Example 4, the number average molecular weight of polylactic acid is 3.0×10 5 g / mol.
[0092] Comparative Example 5 A method for preparing a super-hydrophobic metal-organic framework composite material is basically the same as that in Example 1, except that in Comparative Example 5, ZIF-8 is used instead of NH2-ZIF-67.
[0093] In Comparative Example 5, the preparation method of ZIF-8 adopted is: 0.745 g of zinc nitrate hexahydrate is dissolved in 50 mL of methanol to obtain a zinc nitrate solution. 1.889 g of 2-methylimidazole is dissolved in 50 mL of methanol to obtain a ligand solution. The two solutions are mixed and stirred for 1.5 h to obtain a milky white suspension, which is placed in a centrifuge and centrifuged at a speed of 5000 r / min for 4 min, and washed with methanol, and the centrifugation and washing are repeated three times each, and dried at 80°C for 12 h to obtain a ZIF-8 solid powder, which is recorded as ZIF-8.
[0094] In Comparative Example 5, a super-hydrophobic metal-organic framework composite material was prepared using polylactic acid, which was denoted as modified ZIF-8.
[0095] Comparative Example 6 A method for preparing a hydrophobic metal organic framework composite material is basically the same as that in Example 1, except that in Comparative Example 6, NH2-UiO-66 is used instead of NH2-ZIF-67.
[0096] In Comparative Example 6, the preparation method of NH2-UiO-66 is as follows: 0.9 g zirconium tetrachloride is dissolved in 10 mL of DMF. 0.635 g 2-aminoterephthalic acid is dissolved in 10 mL of DMF. The above solutions are mixed quickly, and 30 mL DMF is added. After mixing evenly, 10 mL of glacial acetic acid is added, followed by stirring for 1 h to make it uniform, and finally reacted in a hydrothermal reactor at 120 ° C for 18 h, washed three times with ethanol, centrifuged at 5000 r / min in a centrifuge for 4 min, and dried at 65 ° C for 12 h to obtain NH2-UiO-66 material, recorded as NH2-UiO-66.
[0097] In Comparative Example 6, a super-hydrophobic metal-organic framework composite material was prepared using polylactic acid, and was recorded as modified NH2-UiO-66.
[0098] The contact angle and rolling angle of the materials prepared in Examples 1-12 and Comparative Examples 1-6 were tested using an S1250 contact angle goniometer. The results are shown in Table 1.
[0099] Table 1 Contact angle data of different materials
[0100] As can be seen from Table 1, the number average molecular weight of polylactic acid is 1.0×10 5 g / mol~2.5×10 5 g / mol. When the mass fraction of polylactic acid in the polylactic acid solution is 0.07wt%~0.2wt%, polylactic acid modification can significantly enhance the hydrophobicity of NH2-ZIF-67 and NH2-ZIF-8, and the contact angle becomes larger. In particular, when the mass fraction of polylactic acid in the polylactic acid solution is 0.1wt%, the number average molecular weight is 1.9×10 5 g / mol, the prepared super-hydrophobic metal-organic framework composite material has the best hydrophobicity; in addition, the reaction time of polylactic acid and NH2-ZIF-67 also affects the hydrophobicity of the material. When the amidation reaction time is 6h to 15h, the prepared composite material has super-hydrophobic properties, especially when the reaction time is 12h, the prepared super-hydrophobic metal-organic framework composite material has the best hydrophobicity.
[0101] As can be seen from Table 1, in Comparative Examples 1 and 2, the contact angles of the samples not modified with polylactic acid are 45° and 50°, both lower than 90°, indicating hydrophilicity.
[0102] As can be seen from Table 1, in Comparative Examples 3 and 4, when NH2-ZIF-67 is modified with polylactic acid having a smaller or larger molecular weight, the hydrophobicity is still poor and excellent hydrophobicity cannot be obtained. In particular, when NH2-ZIF-67 is modified with polylactic acid having a larger molecular weight, part of the polylactic acid easily falls off from NH2-ZIF-67.
[0103] As can be seen from Table 1, the use of polylactic acid modification in Comparative Example 5 can improve the hydrophobicity of ZIF-8 and obtain a superhydrophobic effect, but polylactic acid is difficult to be firmly fixed on the surface of ZIF-8, which makes the modified ZIF-8 material have the defect of poor stability.
[0104] As shown in Table 1, although the comparative example 6 is also modified by polylactic acid, the contact angle of the modified NH2-UiO-66 material is 122°, and the hydrophobic performance is far inferior to that of Example 1. The reason may be that NH2-UiO-66 has larger pores and windows, and water molecules can easily pass through the pores and destroy the structure. At the same time, due to the rich hydroxyl groups in NH2-UiO-66, it has hydrophilicity, which limits its application in occasions where hydrophobic properties are required. In addition, the use of polylactic acid to modify NH2-UiO-66, due to the complex internal pore structure of NH2-UiO-66, easily causes the polymer to block the pores.
[0105] It can be seen that although the surface properties of metal organic framework materials can be changed through chemical modification and other methods, ZIF materials as relatively hydrophobic materials are easier to achieve this goal. This is because ZIF materials have a microporous structure, and the size of these micropores is comparable to the size of water molecules, which makes it impossible for water molecules to pass through these micropores, thereby achieving water repellency.
[0106] In addition, the NH2-ZIF-67 and modified NH2-ZIF-67 prepared in Example 1, the ZIF-8 and modified ZIF-8 prepared in Comparative Example 5, and the NH2-UiO-66 and modified NH2-UiO-66 prepared in Comparative Example 6 were respectively subjected to the following tests: (1) XRD test: The phase and crystal structure of NH2-ZIF-67 and modified NH2-ZIF-67 were tested using a PANalytical EMPYREAN X-ray diffractometer from PANalytical Instruments of the Netherlands.
[0107] (2) Infrared spectroscopy test: The characteristic groups of NH2-ZIF-67 and modified NH2-ZIF-67 were tested using a German Bruker VERTEX 70 FT-IR instrument.
[0108] (3) SEM test: The surface morphology of NH2-ZIF-67 and modified NH2-ZIF-67 was tested using a Quanta 200F scanning electron microscope produced by FEI Company of the Netherlands.
[0109] (4) Contact angle test: The contact angles of NH2-ZIF-67 and modified NH2-ZIF-67 were tested using a S1250 contact angle goniometer.
[0110] (5) Chemical stability test: At room temperature, a small amount of the NH2-ZIF-67 and modified NH2-ZIF-67 prepared above, the ZIF-8 and modified ZIF-8 prepared in Comparative Example 5, and the NH2-UiO-66 and modified NH2-UiO-66 prepared in Comparative Example 6 were respectively added into vials containing acidic and alkaline solutions of pH = 3 and 12 adjusted by HCl and NaOH and immersed for a period of time.
[0111] The test results are as follows: Figure 1 The XRD patterns of NH2-ZIF-67 and modified NH2-ZIF-67 prepared in Example 1 of the present invention are shown in FIG. Figure 1 It can be seen that the XRD pattern of modified NH2-ZIF-67 is consistent with the standard X-ray diffraction Figure 1 This indicates that the superhydrophobic NH2-ZIF-67 crystal structure was successfully formed and the introduction of polylactic acid did not lead to the appearance of new peaks in the structure.
[0112] Figure 2 The infrared spectra of NH2-ZIF-67 and modified NH2-ZIF-67 prepared in Example 1 of the present invention are shown in FIG. Figure 2 It can be seen that the characteristic functional group of imidazole, 2920 cm -1 and 2850cm -1 The symmetric and asymmetric stretching vibration peaks of -CH2- appear at the position, proving that polylactic acid has been successfully grafted onto NH2-ZIF-67.
[0113] Figure 3a-3b The SEM images of NH2-ZIF-67 (a) and modified NH2-ZIF-67 (b) prepared in Example 1 of the present invention are shown in FIG3 . As can be seen from FIG3 , after chemical modification with polylactic acid, the surface morphology of modified NH2-ZIF-67 hardly changes, indicating that chemical modification with polylactic acid has little effect on the surface morphology and size of NH2-ZIF-67.
[0114] Figure 4a-4b Graphs showing the water contact angle test results of NH2-ZIF-67 (a) and modified NH2-ZIF-67 (b) prepared in Example 1 of the present invention. Figure 4aIt can be seen that the contact angle of NH2-ZIF-67 without polylactic acid modification is 45°, which has good hydrophilicity. The contact angle of the modified NH2-ZIF-67 material is 160°, achieving a superhydrophobic effect.
[0115] Figure 5 1 is the XRD diagram of NH2-ZIF-67 and modified NH2-ZIF-67 prepared in Example 1 of the present invention after chemical stability test. Figure 5 It can be seen that the crystallinity of NH2-ZIF-67 was significantly weakened after being immersed in extremely harsh solutions (solutions with pH values of 3 and 12, respectively) for 3 days, indicating that NH2-ZIF-67 has poor resistance to these extremely harsh environments; in contrast, the modified NH2-ZIF-67 still maintains a good crystal structure after being placed in a series of extremely harsh solutions (solutions with pH values of 3 and 12, respectively) for 3 days, indicating that it has excellent ability to resist harsh environments and exhibits very excellent stability.
[0116] Figure 6 The XRD diagrams of ZIF-8 and modified ZIF-8 prepared in Comparative Example 5 after chemical stability testing.
[0117] Figure 7 XRD diagrams of NH2-UiO-66 and modified NH2-UiO-66 prepared in Comparative Example 6 after chemical stability test.
[0118] Depend on Figure 6 and Figure 7 It can be seen that the crystallinity of ZIF-8 and modified ZIF-8, NH2-UiO-66 and modified NH2-UiO-66 is significantly weakened after being immersed in extremely harsh solutions (solutions with pH values of 3 and 12, respectively) for 3 days, indicating that ZIF-8 and modified ZIF-8, NH2-UiO-66 and modified NH2-UiO-66 have poor resistance to these extremely harsh environments, that is, poor stability. The reasons may be: polylactic acid and ZIF-8 are connected together through van der Waals forces, etc., but such a connection method is easily damaged by the external environment, which causes polylactic acid to easily fall off from ZIF-8 and reduce its hydrophobicity; the pore size of NH2-UiO-66 is comparable to that of water molecules, which makes it easy for water molecules to attach. At the same time, its internal pore structure is complex, which easily causes the polymer to block the pore, resulting in a decrease in hydrophobicity and poor stability.
[0119] Embodiment 13 A super-hydrophobic metal-organic framework composite material is used in treating wastewater, purifying air or preparing sensors, specifically using the super-hydrophobic metal-organic framework composite material prepared in Example 1 to treat wastewater, purify air or prepare sensors.
[0120] (1) Oil-water separation: Superhydrophobic metal-organic framework composites are used to treat oily wastewater. The adsorption and hydrophobic properties of superhydrophobic metal-organic framework composites can be used to efficiently remove grease and organic pollutants from water, thereby achieving effective separation of oil and water. It is suitable for industrial wastewater treatment, cleaning up after offshore oil spills, and other fields. The details are as follows: In order to test the oil-water separation performance, a special separator was prepared, which included a glass triangular funnel (tube outer diameter of 90 mm, tube length of 88.4 mm), a beaker, an iron stand and a clamp. During the experiment, the modified NH2-ZIF-67 material prepared in Example 1 was pressed into a thin sheet using two sieve plates and placed in the narrowest part of the funnel neck for oil-water separation testing. In the separation experiment, organic solvents such as dichloromethane, isooctane and isopentane were selected as test samples. In order to accurately evaluate the oil-water separation efficiency, the water content in the obtained filtrate was accurately measured using a Karl Fischer analyzer.
[0121] For better observation, the aqueous solution was dyed purple with crystal violet and the organic solution was dyed red with oil red O. Then, equal volumes of dichloromethane / water and isooctane / water solution were poured into the funnel. Under the action of gravity, the oil moved quickly and stably in the modified NH2-ZIF-67 material, while the water was isolated above the modified NH2-ZIF-67 material, achieving oil-water separation.
[0122] In order to further study the separation efficiency of the modified ZIF material for oil-water mixture, the water content in the separated oil-water mixture was measured by Karl Fischer method. The results are shown in Table 2.
[0123] The separation efficiencies of other organic solvents are shown in Table 2 below.
[0124] Table 2 Summary of oil-water separation results
[0125] As shown in Table 2, the water content in the separated dichloromethane / water mixture and isooctane / water mixture is less than 20 ppm, and the separation efficiency is greater than 99%, which verifies the excellent performance of the modified NH2-ZIF-67 material in the separation of oil-water mixture.
[0126] From the above results, it can be seen that compared with conventional surface-modified metal organic framework materials, the preparation method of the present invention has a number average molecular weight of 1.0×10 5 g / mol~2.5×10 5The polylactic acid of 1000 g / mol is used as a modifier, and the amino-modified ZIF material is modified to prepare a super-hydrophobic metal organic framework composite material with low cost, good hydrophobicity, good stability and environmental protection, which has potential applications in solving the greenhouse effect and industrial gas adsorption and separation, oil-water separation, etc., and has good application prospects in the field of materials science. At the same time, the preparation method of the present invention also has the advantages of simple process, easy operation, mild preparation conditions, etc., is suitable for large-scale preparation, and is convenient for industrial application.
[0127] The above embodiments are only preferred implementations of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a super-hydrophobic metal-organic framework composite material, characterized in that: The following steps are involved: S1. providing an amino-modified ZIF material; the amino-modified ZIF material comprises at least one of NH2-ZIF-67 and NH2-ZIF-8; S2, mixing the amino-modified ZIF material with polylactic acid for amidation reaction to obtain a super-hydrophobic metal organic framework composite material; the number average molecular weight of the polylactic acid is 1.0×10 5 g / mol~2.5×10 5 g / mol.
2. The preparation method according to claim 1, characterized in that In step S2, the number average molecular weight of the polylactic acid is 1.5×10 5 g / mol~2.0×10 5 g / mol.
3. The preparation method according to claim 2, characterized in that: In step S2, the polylactic acid is mixed with the amino-modified ZIF material in the form of a polylactic acid solution; The ratio of the mass of the amino-modified ZIF material to the volume of the polylactic acid solution is 0.2 mg to 0.7 mg: 1 mL; The polylactic acid solution is prepared by dissolving polylactic acid in dichloromethane; the mass fraction of the polylactic acid in the polylactic acid solution is 0.07wt% to 0.2wt%.
4. The preparation method according to claim 3, characterized in that The ratio of the mass of the amino-modified ZIF material to the volume of the polylactic acid solution is 0.3 mg to 0.6 mg: 1 mL; The mass fraction of the polylactic acid in the polylactic acid solution is 0.1 wt % to 0.15 wt %.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S1, the preparation method of NH2-ZIF-67 comprises the following steps: (1.1) Dissolve a cobalt salt in methanol to prepare a cobalt salt solution; dissolve 2-aminobenzimidazole and 2-methylimidazole in methanol to obtain a ligand solution A; the ratio of the cobalt salt to the methanol is 0.5 g to 0.8 g: 50 mL; the cobalt salt is cobalt nitrate hexahydrate; the ratio of the 2-aminobenzimidazole to the 2-methylimidazole to the methanol is 0.4 g to 0.6 g: 1 g to 1.4 g: 50 mL; (1.2) Mix the cobalt salt solution and ligand solution A, stir for 1 h to 2 h, centrifuge at 4500 r / min to 6000 r / min for 3 min to 5 min, wash with methanol, repeat the centrifugation and washing three times each, and dry at 40°C to 80°C for 10 h to 15 h to obtain NH2-ZIF-67 solid powder.
6. The preparation method according to any one of claims 1 to 4, characterized in that: In step S1, the preparation method of NH2-ZIF-8 comprises the following steps: (2.1) Dissolve a zinc salt in methanol to prepare a zinc salt solution; dissolve 2-aminobenzimidazole and 2-methylimidazole in methanol to obtain a ligand solution B; the ratio of the zinc salt to methanol is 0.6 g to 0.8 g: 50 mL; the zinc salt is zinc nitrate hexahydrate; the ratio of the 2-aminobenzimidazole to the 2-methylimidazole to the methanol is 0.4 g to 0.6 g: 1 g to 1.4 g: 50 mL; (2.2) Mix the zinc salt solution and ligand solution B, stir for 1 h to 2 h, centrifuge at 4500 r / min to 6000 r / min for 3 min to 5 min, wash with methanol, repeat the centrifugation and washing three times each, and dry at 40°C to 80°C for 10 h to 15 h to obtain NH2-ZIF-8 solid powder.
7. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the amidation reaction is carried out at a temperature of 30°C to 60°C; the amidation reaction time is 6h to 15h; after the amidation reaction is completed, the product is subjected to the following treatment: centrifugation at a speed of 4500 r / min to 6000 r / min for 3 min to 5 min, washing with ethanol, and drying at 40°C to 80°C for 10 h to 15 h to obtain a superhydrophobic metal-organic framework composite material.
8. The preparation method according to claim 7, characterized in that: In step S2, the amidation reaction is carried out at a temperature of 40°C to 50°C; and the amidation reaction time is 8h to 12h.
9. A super-hydrophobic metal-organic framework composite material, characterized in that: The super-hydrophobic metal-organic framework composite material is prepared by the preparation method described in any one of claims 1 to 8.
10. Use of the superhydrophobic metal-organic framework composite material as claimed in claim 9 in treating wastewater, purifying air or preparing sensors.
Citation Information
Patent Citations
Metal-organic framework material having hydrophobic surface, and preparation method and application thereof
CN107722287A
Metal-organic framework material with hydrophobic surface and preparation method and applications thereof
CN108948367A
Preparation method of ZIF-8 / polylactic acid composite porous material and product thereof
CN112619618A
Method and apparatus for acquirising vulnerability feature, and electronic device
KR1020210042285A
Metal-organic framework functionalized polymeric compositions
US20170028390A1
Cited By
Composite membrane as well as preparation method and application thereof
CN120169190A